2017
DOI: 10.1186/s12888-017-1453-5
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and suicide attempts with and without psychiatric disorders: analysis of impulsivity and neuroticism

Abstract: BackgroundThere is a critical need for empirical data concerning the association of personality traits and attempted suicide with and without psychiatric disorders in mainland China. The objective of the present study is to provide such data by determining the prevalence of psychiatric disorders and analyzing the levels of impulsivity and neuroticism among people who have attempted suicide, and to examine the association between these personality traits and suicide attempt in people with or without psychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 48 publications
4
16
0
2
Order By: Relevance
“…In another study by Soma and Sadhan (2011) indicated that most students had reported 75.5% cases of suicide attempts and at the sometime the prevalence rates were significantly higher in females not living with both parents, not in the Island. Similarly, Bi et al (2017) also reported cases of ideation and Suicide attempts among the patients admitted into the psychiatric hospital in china. Whereas, Swanson and Colman (2011) showed in their finding that parental attempts to suicidal cases had contributed up to 3.5 increases in youth's probability of having suicidal thoughts with a 2.6 increased chance of them attempting suicide.…”
Section: Literature Reviewmentioning
confidence: 85%
“…In another study by Soma and Sadhan (2011) indicated that most students had reported 75.5% cases of suicide attempts and at the sometime the prevalence rates were significantly higher in females not living with both parents, not in the Island. Similarly, Bi et al (2017) also reported cases of ideation and Suicide attempts among the patients admitted into the psychiatric hospital in china. Whereas, Swanson and Colman (2011) showed in their finding that parental attempts to suicidal cases had contributed up to 3.5 increases in youth's probability of having suicidal thoughts with a 2.6 increased chance of them attempting suicide.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Maybe some related personality traits or perceived stress are potential mediators for such link. Firstly, personality traits can affect emotional perception, decision-making, and then behavior [42]. For example, Peters et al reported that impulsivity was associated with suicide attempt [43].…”
Section: Discussionmentioning
confidence: 99%
“…(2016)reported that there was a significant positive correlation between neuroticism and impulsivity, and that both traits were correlated with binge eating. Neuroticism and impulsivity in individuals usually manifest as emotional instability, lack of control, anxiety, depression, binge eating, suicide attempts, and other maladaptive psychological behaviors (Bi et al., 2017; Lee-Winn et al., 2016). Individuals with high neuroticism demonstrate the tendency to show intense emotional responses (Brunault et al., 2018).…”
Section: Introductionmentioning
confidence: 99%